Determinants of the duration of birth intervals in Tanzania: Regional contrasts and temporal trends - Yoder, P. Stanley; Lugalla, Joe L.P.; Sambaiga, Richard F. (DHS Qualitative Research Studies No. 19, 2013)
The duration of birth intervals has received attention in demography and public health research because of its implication for fertility and for maternal and child health. This study examines the duration of birth intervals in two regions of Tanzania and seeks to explain the origin of the differences between the regions by considering survey data as well as interviews with individual women and groups of men. Our starting point is the striking regional trends in the length of birth intervals as observed in the five Tanzanian surveys of the Demographic and Health Surveys Program that have been conducted in the country from 1991 to 2010. In particular this study focuses mainly on the populations of Western and Southern Zones, where the DHS also showed contrasts in the contraceptive prevalence rate (CPR) for modern methods over time. In the Western Zone, the CPR was 2% in 1991, and then 7% for the next three surveys, eventually rising to 13% in the 2010 survey. In the Southern Zone, the CPR was 4% in 1991 and rose substantially in each survey until it reached 36% in 2010. These two zones present stark contrasts in both the duration of birth intervals and in the use of contraception.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This study was carried out with support provided by the United States Agency for International Development (USAID) through the MEASURE DHS project (#GPO-C-00-08-00008-00). The views expressed are those of the authors and do not necessarily reflect the views of USAID or the United States Government. Additional information about the MEASURES DHS project can be obtained by contacting MEASURE DHS, ICF Macro, 11785 Beltsville Drive, Suite 300, Calverton, MD 20705 (telephone: 301-572-0200; fax 301-572-0999; email: reports@measuredhs.com; internet: www.measuredhs.com).